). AMINO ACID COMPOSITION AND ANTIOXIDANT PROPERTIES OF FIVE EDIBLE MUSHROOM SPECIES FROM KASTAMONU, TURKEY - Kan Bakır, Temel; Boufars, Mansor; Karadeniz, Mertcan; Ünal, Sabri (African Traditional Herbal Medicine Supporters Initiative (ATHMSI), 2018)
Background: Hydnum repandum, Cantharellus cibarius, Ramaria fennica, Boletus edulis, and Craterellus cornucopioides are all wild edible mushroom species from the Kastamonu province. The aim of this study was to investigate antioxidant properties and amino acid contents of these mushrooms.
Materials and Methods: The mushrooms were analyzed for their free amino acid compositions using a high performance Amino Acid analyzer (Biochrom 30). Also, antioxidant activity and total phenolic concentrations of five different mushroom species were studied by using spectrophotometric methods.
Results: The mushrooms contained 17 amino acids (g/100 g): Glutamic acid (2.56–1.11), Alanine (1.49–0.54), Arginine (1.62–6.77), Aspartic acid (1.45–0.81), Leucine (1.08–0.64), Methionine (1.05–0.06), Valine (1.05–0.66), Lysine (1.01–0.57), Serine (0.68–0.38), Cysteine (0.88–0.11), Isoleucine (0.61–0.39), Glycine (0.82–0.35), Threonine (0.82–0.44), Phenylalanine (0.66–0.42), Proline (0.60–0.47), Tyrosine (0.58–0.38), and Histidine (0.48–0.22). The total free amino acid (TAA) contents ranged from 169.2 mg/g in Boletus edulis to 89.1 mg/g in Hydnum repandum. These five different mushroom species contain eight essential amino acid species except tryptophan. The antioxidant activity of mushroom extracts was expressed as the percentage of DPPH radical inhibition and IC50 values (mg/mL). The percentage of inhibition ranged from 2.38% to 88.05% and IC50 values ranged from 0.03 to 13.98 mg/mL. The total phenolic content ranged from 0.66 to 7.74 mg/g of dry mushroom extract, expressed as gallic acid equivalents.
Conclusion: Methanolic extract of Boletus edulis showed the highest phenolic content and strong antioxidant activity. As a result, the significant linear correlation between the values for the total phenolic content and antioxidant activity of mushroom extracts was corroborated in all of the investigated mushroom species, with the exception of Craterellus cornucopioides.
Keywords: Edible mushrooms, Amino acids, Total phenolics, Antioxidant properties, Kastamonu